PENGARUH LAMA PENYIMPANAN TERHADAP KUALITAS SAGU SEP DAGING RUSA (Cervus timorensis) DENGAN METODE BAKING - Iyoseina Maranatha; A. Tenny Damayanti Indriastuti; Henny V Saiya (Faculty of Agriculture, Musamus University, 2019)
This study aims to determine the baking method effect the to shelf life of meat sep sago deer (Cervus timorensis). This research was conducted in the laboratory of Animal Husbandry Musamus Merauke.. The perameters observed in this study is the physical testing of the storage time (flavor, color, texture, slimy) with storage treatment for 1 day, 2days, and 3 days and test bacteria (Coliform and Escherechia coli). The results of physical testing of the shelf life showed the physical quality of sago sep after 1 day storage changed into slimy, rancid, the color begins to changed, and moldy. Key words : deer meat; sago sep; shelf